Into the wild—WAMBAM goes to Canada. Issue 5 (31st March 2018) - Morrissey, Michael B.; Janeiro, Maria João; Sparks, Alexandra M.; White, Stephen; Pigeon, Gabriel; Teplitsky, Céline; Réale, Denis; Milot, Emmanuel
Abstract : The sixth Wild Animal Models Bi‐Annual Meeting was held in July 2017 in Québec, with 42 participants. This report documents the evolution of questions asked and approaches used in evolutionary quantitative genetic studies of wild populations in recent decades, and how these questions and approaches were represented at the recent meeting. We explore how ideas from previous meetings in this series have developed to their present states, and consider how the format of the meetings may be particularly useful at fostering the rapid development and proliferation of ideas and approaches.